Echoes of Female Survivals in Hellenistic-Era Elegy: the Case of Edile of Samos (Altre Modernità, 2025)
This research aims to analyze the fragments on the production of the Hellenistic age’s poet, Edyle of Samos. Information on this poet is very limited and vague, but it is known that she wrote an elegiac poem entitled “Scylla”, which perhaps narrated Glaucus’ unrequited love for the siren Scylla. Although only a fragment has survived, it is possible to assume that Edyle’s poem was used as a model for other elegiac poems during the Hellenistic and Roman ages. Scylla’s story, in fact, is also narrated by Aeschrion of Samos (SH 5) and Alexander Aetolus (Fr. 1 Powell) and by Ovid, in Metamorphoseon Libri XV. Thus, by comparing the “Scylla” fragment with fragments of Hellenistic and Roman elegiac compositions, an attempt will be made to understand whether Edyle’s poem was a model for later poets. Finally, we will try to understand why Edyle’s poem disappeared over the centuries.
Keywords: Hellenistic elegy; Hellenistic literature; Imperial Elegy; Edyle; Ovid; poetic models